The Different Inhibition of Return (IOR) Effects of Emergency Managerial Experts and Novices: An Event-Related Potentials Study - Cao, Rong; Wu, Lü; Wang, Shuzhen (Frontiers in Behavioral Neuroscience, 2017)
Inhibition of return (IOR) is an important effect of attention. However, the IOR of emergency managerial experts is unknown. By employing emergency and natural scene pictures in expert-novice paradigm, the present study explored the neural activity underlying the IOR effects for emergency managerial experts and novices. In behavioral results, there were no differences of IOR effects between novices and emergency managerial experts, while the event-related potentials (ERPs) results were different between novices and experts. In Experiment 1 (novice group), ERPs results showed no any IOR was robust at both stimulus-onset asynchrony (SOA) of 200 ms and 400 ms. In Experiment 2 (expert group), ERPs results showed an enhanced N2 at SOA of 200 ms and attenuated P3 at cued location in the right parietal lobe and adjacent brain regions than uncued location at SOA of 200 ms. The findings of the two experiments showed that, relative to the novices, IOR for the emergency managerial experts was robust, and dominated in the right parietal lobe and adjacent brain regions, suggesting more flexible attentional processing and higher visual search efficiency of the emergency managerial experts. The findings indicate that the P3, possible N2, over the right parietal lobe and adjacent brain regions are the biological indicators for IOR elicited by post-cued emergency pictures for emergency managerial experts.